Sequence diagram synthesis theory for stitching together multiple sequence diagrams through formal semantics modelling - Ameedeen, Mohamed Ariff (2010)
Synthesis of UML Sequence Diagrams, where various component models are put together to create a larger, more holistic Sequence Diagrams is a widely-studied area of research. However, there is no unifying theory that proves that the synthesis could be performed without losing any vital data, or introducing any inherent behaviour. The objective of this research is to produce a Sequence Diagram Synthesis Theory that would enable various components of Sequence Diagrams to be synthesized into a mathematically proven, semantically equivalent, holistic Sequence Diagram. This theory will be based on Formal Semantics Modelling, using the concept of Model Driven Development (MDD) Model Transformation. MDD Model Transformation allows Sequence Diagrams to be transformed into Petri Nets, a formal, mathematical language with a strong theory of synthesis. This theory would have to be engineered to work with Sequence Diagrams in order to produce the Sequence Diagram Synthesis Theory. This theory will be evaluated using a common sematics domain between Sequence Diagrams and Petri Nets called Labelled Event Structures. The evaluation should mathematically prove that there are no data loss or introduction of inherent behaviour during the composition. This research is expected to produce a theory of Sequence Diagram Synthesis, where various Sequence Diagrams may be put together or composed into a singular, more holistic Sequence Diagram that is entirely accurate, without any data loss. This theory can then be applied into various areas of research that could utilize model synthesis. An example application is in Green Computing, where models may be reused and stitched together using this theory instead of remodelling the whole Sequence Diagram. In a manufacturing example, different Sequence Diagrams describing different configuration may be plugged into a Standard Operating Procedure (SOP) using this theory to check the behaviour of each configuration.